1980
DOI: 10.3177/jnsv.26.367
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipid synthesis in rat adipose tissue during development.

Abstract: SummaryLipogenesis in rat adipose tissue during postnatal develop ment has been studied by measuring the incorporation of labeled glucose into lipid in fat cells and the activities of certain enzymes which participate in lipogenesis. It was found that: (1) Fatty acid synthesis from glucose is negligible in the suckling period. After weaning, it increases rapidly and reaches a plateau at the age of 10 weeks. (2) Insulin sensitivity is negligible in the suckling period. After weaning it rises and then declines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…In adipose tissue, age has been shown to influence basal lipolytic activity (Gruen et al, 1980), lipogenesis (Tsujikawa and Kimura, 1980) , the activity of individual enzymes involved in lipolysis (Cooper and Gregerman, 1976) as well as lipolytic responses to hormones (Hartman and Christ, 1978;Holm et al, 1975). Thus, progestin effects may be governed by changes in adipose tissue metabolism but not necessarily through adult mechansism; for example, ovarian steroids appear to have no effect on lipolysis in adult animals (Steingrimsdottir al^.…”
Section: The Paradox Of Progesterone Treatment In Weanling Ratsmentioning
confidence: 99%
“…In adipose tissue, age has been shown to influence basal lipolytic activity (Gruen et al, 1980), lipogenesis (Tsujikawa and Kimura, 1980) , the activity of individual enzymes involved in lipolysis (Cooper and Gregerman, 1976) as well as lipolytic responses to hormones (Hartman and Christ, 1978;Holm et al, 1975). Thus, progestin effects may be governed by changes in adipose tissue metabolism but not necessarily through adult mechansism; for example, ovarian steroids appear to have no effect on lipolysis in adult animals (Steingrimsdottir al^.…”
Section: The Paradox Of Progesterone Treatment In Weanling Ratsmentioning
confidence: 99%
“…However, RAB18 expression exhibited a marked increase during puberty, reaching the highest levels at P45 and remaining elevated thereafter. This age-related increase in RAB18 expression coincides with the period of highest adipocyte hypertrophy in rat WAT, which occurs between P40 and P80 and is characterized by an increase in the lipogenic activity and a decline in the lipolytic rate of adipocytes (Tsujikawa & Kimura 1980, Herrera & Amusquivar 2000. Accordingly, it has been reported that Rab18 mRNA expression and protein content increased in 3T3-L1 adipocytes as these cells accumulated lipids during differentiation (Pulido et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…The low concentration of plasma insulin during the suckling period could limit adipose tissue lipoprotein lipase activity and the marked increases of plasma insulin after weaning could play an important role in activation of lipoprotein lipase (Cryer, 1982). The rates of glucose utilization in vivo and of lipogenesis are very low in white adipose tissue during the suckling period and markedly increase after weaning onto a highcarbohydrate (HC) diet (Hahn, 1970;Tsujikawa & Kimura, 1980;Gandemer et al 1982;Issad et al 1988). Basal and insulin-stimulated glucose metabolism are also very low in isolated adipocytes during the suckling period but increase markedly after weaning onto a high-fat (HF) diet (Tsujikawa & Kimura, 1980;Issad et al 1989).…”
Section: By D O M I N I Q U E P E R D E R E a U L F A B I E N N E Fmentioning
confidence: 99%
“…Basal and insulin-stimulated glucose metabolism are also very low in isolated adipocytes during the suckling period but increase markedly after weaning onto a high-fat (HF) diet (Tsujikawa & Kimura, 1980;Issad et al 1989). In contrast, weaning onto an HF diet entirely prevents the increase in the rate of glucose utilization in vivo, in the rate of lipogenesis and the increase in sensitivity to insulin of white adipose tissue (Tsujikawa & Kimura, 1980;Issad et al 1988Issad et al , 1989. The aim of the present paper is to review the nutritional and hormonal factors involved in the regulation of lipogenic enzyme gene expression in adipose tissue during the suckling-weaning transition,.…”
Section: By D O M I N I Q U E P E R D E R E a U L F A B I E N N E Fmentioning
confidence: 99%
See 1 more Smart Citation